Esophageal Anomalies, Diverticula, Atresia, Stenosis, Achalasia, Causes and their Current Solutions - qizi, Ganjiyeva Munisa Komil (American Journal of Biomedicine and Pharmacy, 2025)
Esophageal developmental anomalies are disorders of the embryonic development of the esophagus, leading to the formation of an anatomically and histologically incorrect structure of the organ. This manifests itself as dysphagia and inability to accept enteral nutrition. Pathologies are often accompanied by respiratory symptoms: cough, varying degrees of shortness of breath. Aspiration pneumonia may develop. Diagnosis of esophageal developmental anomalies is made on the basis of clinical signs of developmental defects; radiological and endoscopic confirmation is required. Treatment is carried out using surgery, plastic surgery, and in some cases, intestinal tissue grafts.